Chemical design enables the control of conformational polymorphism in functional 2, 3-thieno(bis)imide-ended materials. Issue 11 (5th January 2015) - Maini, Lucia; Gallino, Federico; Zambianchi, Massimo; Durso, Margherita; Gazzano, Massimo; Rubini, Katia; Gentili, Denis; Manet, Ilse; Muccini, Michele; Toffanin, Stefano; Cavallini, Massimiliano; Melucci, Manuela
Abstract : We introduce a chemical design strategy to control conformational polymorphism in 2, 3-thienoimide based molecular materials. Abstract : We report a successful chemical design strategy based on the even–odd alkyl end tailoring, which allows us to promote and control conformational polymorphism in single crystal and thin deposits of thienoimide-based molecular semiconductors (C x -NT4N).